Effect of carboxyethylation degree on the adsorption capacity of Cu(II) by N-(2-carboxyethyl)chitosan from squid pens. (15th March 2016) - Huang, Jun; Xie, Haihua; Ye, Hui; Xie, Tian; Lin, Yuecheng; Gong, Jinyan; Jiang, Chengjun; Wu, Yuanfeng; Liu, Shiwang; Cui, Yanli; Mao, Jianwei; Mei, Lehe
Highlights: N -CECS was synthesized from squid pen β-chitin as starting materials. The adsorption capacity of Cu(II) correlated well with the DS of N -CECS. The highest adsorption capacity of Cu(II) among three N -CECS reached 207.5 mg g −1 . Chemisorption was the rate-controlling step for Cu(II) adsorbed onto N -CECS. Abstract: Chitosan was prepared by N -deacetylation of squid pens β-chitin, and N -carboxyethylated chitosan ( N -CECS) with different degrees of substitution (DS) were synthesized. DS values of N -CECS derivatives calculated by 1 H nuclear magnetic resonance (NMR) spectroscopy were 0.60, 1.02 and 1.46, respectively. The adsorption capacity of Cu(II) by N -CECS correlated well with the DS and pH ranging from 3.2 to 5.8. The maximum Cu(II) adsorption capacity ( q m ) of all three N -CECS at pH 5.4 was 207.5 mg g −1, which was 1.4-fold higher than that of chitosan. The adsorption equilibrium process was better described by the Langmuir than Freundlich isotherm model. Adsorption of Cu(II) ion onto N -CECS followed a pseudo-second order mechanism with chemisorption as the rate-limiting step. In a ternary adsorption system, the adsorption capacity of Cu(II) by N -CECS also presented high values, and q m for Cu(II), Cd(II), and Pb(II) were 150.2, 28.8, and 187.9 mg g −1, respectively.